Analysis of Drag Reduction Due to Hydrophobic Coating Application by Experiment - Rizki Aulia Chandra Putera; Muhammad Luqman Hakim; Untung Budiarto; S. Samuel (International Journal of Marine Engineering Innovation and Research, 2023)
Nowaday, at least 80% of the world's cargo is shipped via marine transportation modes, so with the amount of shipping activity, the shipping industry produces air pollution of at least 3.3% of global carbon dioxide emissions. The problem is trying to be answered by reducing a fuel use, one of which is through drag reduction. It is estimated that at least 80-90% of the drag that occurs on VLCC (Very Large Crude Carrier), comes from frictional drag that occurs on the surface of the hull. One of method to reducing frictional drag is by applying a hydrophobic coating. The hydrophobic coating has molecular physical properties to repel water. Similar as the water on a lotus leaf that can’t wet the leaves even a little, this phenomenon is called the Hydrophobic effect. Applying the hydrophobic coating on the specimen is done by spraying hydrophobic coating paint. As It seen from the contact angle with value above 900 shows the hydrophobic effect on the coated surface. This research aims to prove whether the application of hydrophobic coating on the hull specimen would give a significant effect such as buoyancy increase and drag reduction characteristics. The research method used is the experimental method by pulling the ship model utilizing the free fall of the load mass to provide a pulling force to the ship model and hydrophobic evaluation of the surface. The experiment was carried out in the Diponegoro University’s hydrodynamics lab with the assumption that the increase in acceleration is a drag reduction. From the test results, it was found that the drag reduction value has a percentage above 25% with the use of light mass variations. In the experiment, there is phenomenon of buoyancy increase characteristic appeared after the appliance of hydrophobic coating.